Peran Pengambil Kebijakan dan Masyarakat dalam Pencegahan Penularan Filariasis (Studi Kualitatif) - Santoso Santoso; Yahya Yahya; Yulian Taviv; Katarina Sri Rahayu; Yanelza Supranelfi; Vivin Mahdalena; Rizki Nurmaliani; Maya Arisanti; Marini Marini; Nungki Hapsari Suryaningtyas; I Gede Wempi Dody Surya Permadi; Tri Wurisastuti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
Filariasis is still a health problem in East TanjungJabung and Belitung regencies even though mass treatment activities have been carried out for five rounds. Both districts are still endemic for filariasis because the Microfilaria rate (Mf rate) is still more than 1%. This study aims to identify the role of the community of various parties in controlling filariasisin Tanjung Jabung Timur and Belitung regencies. The research design is descriptive with a qualitative approach. Informants for the in-depth interviews were health workers at the district, sub-district and village levels as well as the village community. The number of health worker informants was 10 people, 16 community leaders, 16 cadres, and 9 sufferers, while the FGD consisted of 4 groups. Each group consists of 7 participants. Data was collected through in-depth interviews and group discussions and the data were analyzed qualitatively. Recruitment of informants for determining in-depth interviews using the snow ball method. The results showed that the roles of officers and policy makers in TanjungJabung Timur Regency were quite good, but in Belitung Regency they were less involved. Meanwhile, the role of community leaders in Indonesia is still not optimal in controlling filariasisespecially in disseminating information about filariasis. Therole of community leaders in East Tanjung Jabung Regency is more powerful than Belitung Regency. Filariasis control activities still need support from policy makers in allocating budgets and the role of community leaders to mobilize the community to be actively involved in controlling filariasis.